2012
DOI: 10.1155/2012/294571
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Penetration through Cracks in High-Performance Concrete and Surface Treatment System for Crack Healing

Abstract: For enhancing the service life of concrete structures, it is very important to minimize crack at surface. Even if these cracks are very small, the problem is to which extend these cracks may jeopardize the durability of these decks. It was proposed that crack depth corresponding with critical crack width from the surface is a crucial factor in view of durability design of concrete structures. It was necessary to deal with chloride penetration through microcracks characterized with the mixing features of concre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…and presence of cracks [45]. Literature is mainly focused on corrosion arising from cracking process [20,51,34]. There are three main consequences of corrosion in SFRC associated to the cracking process: (1) a decrease of the carrying capacity and energy absorption performance of the SFRC element (more brittle behavior); (2) due to the rust formation from fiber corrosion process, fiber-paste friction can increase, enhancing the fiber pullout response, with beneficial effects in terms of load carrying capacity and energy absorption of the SFRC element; (3) if the crack width is small enough that self-healing almost restores SFRC integrity, fiber corrosion has negligible influence in terms of structural and durability performance [20].…”
Section: Corrosion Resistance Of Sfrsccmentioning
confidence: 99%
“…and presence of cracks [45]. Literature is mainly focused on corrosion arising from cracking process [20,51,34]. There are three main consequences of corrosion in SFRC associated to the cracking process: (1) a decrease of the carrying capacity and energy absorption performance of the SFRC element (more brittle behavior); (2) due to the rust formation from fiber corrosion process, fiber-paste friction can increase, enhancing the fiber pullout response, with beneficial effects in terms of load carrying capacity and energy absorption of the SFRC element; (3) if the crack width is small enough that self-healing almost restores SFRC integrity, fiber corrosion has negligible influence in terms of structural and durability performance [20].…”
Section: Corrosion Resistance Of Sfrsccmentioning
confidence: 99%
“…Environmental temperature surrounding the system will also influence chloride binding isotherms. Freundlich binding isotherm (nonlinear binding isotherm) is effective in describing the relation between free chloride and bound chloride at a wide concentration range [15][16][17][18][19][20][21][22][23][24]. The equation of Freundlich binding isotherm is shown as follows [15][16][17][18][19][20][21][22][23][24]:…”
Section: Theoretical Background About Chloride Diffusion Modelmentioning
confidence: 99%
“…Some researchers studied another benefit of surface treatment. For example, Yoon [15] tested chloride penetration through cracks in highperformance concrete and surface treatment system for crack healing. ey concluded that penetrant could not cure cracks; however, coating and combined treatment could prevent chloride from flowing in concrete with maximum crack width of 0.06 mm and 0.08 mm, respectively.…”
Section: Introductionmentioning
confidence: 99%